Defining and evaluating stability in early years assessment. Issue 2 (15th March 2021) - Frans, Niek; Post, Wendy; Oenema-Mostert, Ineke; Minnaert, Alexander
ABSTRACT: Stability is an important underlying assumption in any form of assessment-supported decision-making. Since early years development is frequently described as unstable, the concept plays a central role in the discussion surrounding early years assessment. This paper describes stability as a set of assumptions about the way individual scores change over time. Here, an analytical framework developed by Tisak and Meredith, which can be used to evaluate these assumptions, is extended and applied to evaluate the stability of mathematics scores of 1402 children between kindergarten and third grade. Multilevel models are used to evaluate the assumption that each child has a unique individual growth rate, as well as the assumption that the ranking of children's test scores is consistent over time. The results show that for a large proportion of the children, assuming unique individual growth rates leads to similar predictions as assuming that children develop at an equal pace. While individual differences in growth rate may provide relevant information, these differences only become apparent after several test administrations. As such, decisions should not be based on perceived stagnated or accelerated growth over a short period.